Three Cases of Joubert Syndrome in a Consanguineous Syrian Family and a Interesting Case of Multinational Collaboration - Petrović, Davor; Čulić, Vida; Swinderek-Alsayed, Zofia (Journal of Pediatric Genetics, 2021)
Joubert syndrome (JS) is a rare congenital, autosomal recessive disorder characterized by a distinctive brain malformation, developmental delay, ocular motor apraxia, breathing abnormalities, and high clinical and genetic heterogeneity. We are reporting three siblings with JS from consanguineous parents in Syria. Two of them had the same homozygous c.2172delA (p.Trp725Glyfs*) AHI1 mutation and the third was diagnosed prenatally with magnetic resonance imaging. This pathogenic variant is very rare and described in only a few cases in the literature. Multinational collaboration could be of benefit for the patients from undeveloped, low-income countries that have a low-quality health care system, especially for the diagnosis of rare diseases.
Keywords: Joubert syndrome; consanguineous family; AHI1 mutation